An environmental DNA‐based method for monitoring spawning activity: a case study, using the endangered Macquarie perch (Macquaria australasica). Issue 5 (7th February 2017) - Bylemans, Jonas; Furlan, Elise M.; Hardy, Christopher M.; McGuffie, Prudence; Lintermans, Mark; Gleeson, Dianne M.
Summary: Determining the timing and location of reproductive events is critical for efficient management of species. However, methods currently used for aquatic species are costly, time intensive, biased and often require destructive or injurious sampling. Hence, developing a non‐invasive sampling method to accurately determine the timing and location of reproduction for aquatic species would be extremely valuable. We conducted an experimental and field study to determine the influence of spawning, and the mass release of spermatozoa in particular, on environmental DNA (eDNA) concentrations. Using a quantitative PCR approach we monitored changes in nuclear and mitochondrial eDNA concentrations over time. The data from the experimental study and the field survey supported our hypothesis that spawning events are characterized by higher concentrations of nuclear relative to mitochondrial eDNA. Outside of the reproductive period, we find that nuclear and mitochondrial DNA fragments are equally abundant in environmental water samples. We have shown that changes in the relative abundance of nuclear and mitochondrial eDNA can be used to monitor spawning activity of the endangered Macquarie perch. Our method is likely to be transferrable to other aquatic species and can be particularly useful to increase our understanding of the spawning biology of cryptic, rare or threatened species as well as design and evaluate environmental management actions and determine species establishment.